Optimalisasi Pelayanan Penyaluran Dana Zakat melalui Bank Syariah Indonesia untuk Pemberdayaan Masyarakat di Nagari Batu Banyak - Gina Safitri; Edi Rosman (Lembaga Yasin AlSys, 2026)
Optimizing zakat fund distribution services through Islamic financial institutions plays an important role in increasing the effectiveness of zakat management and community empowerment. Although this issue has been widely studied, research that specifically discusses zakat fund distribution services through Bank Syariah Indonesia in the context of rural communities, particularly in Nagari Batu Banyak, remains limited. This study aims to analyze public awareness and understanding of zakat distribution through Bank Syariah Indonesia, identify the factors that influence public trust in the zakat management system, and analyze limited access to services in supporting community empowerment. This study employed a qualitative approach with a case study design, involving informants consisting of Bank Syariah Indonesia representatives, muzakki, and mustahik selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results show that public awareness and understanding of Bank Syariah Indonesia’s zakat services remain low, public trust in zakat management is not yet optimal, and limited access to services is a major factor hindering the optimization of zakat distribution and community empowerment. These findings strengthen studies on zakat service quality and community empowerment from the perspective of Islamic economics. The conclusion of this study emphasizes the importance of improving zakat literacy, transparency in fund management, expanding access to services, and collaboration between Bank Syariah Indonesia, the nagari government, and community leaders to enhance the effectiveness of zakat management. The implications of the study include theoretical contributions to the development of Islamic economics studies and practical implications for Islamic financial institutions in optimizing zakat services based on rural community empowerment.